MANAGEMENT OF NOTOEDRES CATI AND FELICOLA SUBROSTRATUS INFESTATION IN A MALE CAT - Angela Ivanka Benedicta; Sri Kayati Widyastuti; I Gusti Made Krisna Erawan (Buletin Veteriner Udayana, 2025)
Scabies is a skin disease caused by Notoedres cati mites that is transmitted to cats. Felicola subrostratus is a species of chewing or biting lice that is common in homeless animals or animals in shelters. A domestic cat was examined at the Veterinary Internal Medicine Laboratory, Faculty of Veterinary Medicine, Udayana University with a history of hair loss and itching. The results of the clinical examination showed crusts on the ears, neck, and extremities, accompanied by dandruff on the neck and back areas. Microscopic examination of skin scrapings found Notoedres cati mites. Trichogram examination found Felicola subrostratus lice and eggs. Based on the history, symptoms, physical examination, and supporting examinations, the case cat was diagnosed with scabiosis and Felicola subrostratus infestation with a fausta prognosis. Treatment with ivermectin injection 0.2 mg/kg subcutaneously with two administrations at 14-day intervals. Symptomatic therapy in the form of diphenhydramine HCl 1 mg/kg BW intramuscularly given once a day for two consecutive days and supportive therapy given fish oil for 14 days. Cats are bathed with sulfur soap twice a week. Topical fipronil is given on the 14th day to kill eggs and adult fleas. The treatment given showed good results.